Development and Validation of a Reversed-Phase HPLC Method for the Analysis of Nimodipine in Pharmaceutical Dosage Forms - Krishnaiah, Y.S.R.; Bhaskar, P.; Jayaram, B.; Rama, B.; Raju, V.; Murali Mohan Rao, P. (Asian Journal of Chemistry, 2010)
A rapid and sensitive high-performance liquid chromatographic method was developed for the estimation of nimodipine in pharmaceutical dosage forms. Nimodipine was chromatographed on a reverse phase C-18 column in a mobile phase consisting of acetonitrile and water in the ratio of 58 : 42 (v/v). The mobile phase was pumped at a flow rate of 1 mL/min and the eluents were monitored at 241 nm. The calibration curve was linear in the range of 0.1-40 μg/mL. The intra- and inter-day variation was found to be less than 1 % showing high precision of the assay method. The mean recovery of the drug from the solution containing 10 μg/mL was 99.95 ± 0.86% indicating high accuracy of the proposed HPLC method. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining nimodipine in bulk drug samples and pharmaceutical dosage forms.